History and overview of solar heat technologies - Beattie, Donald A.; IEEE Xplore (Online Service); MIT Press (Cambridge, Massachusetts : MIT Press, 1997)
This final volume in a series that has surveyed advances in solar energy research since the oil shock of the early 1970s provides a broad overview of the U.S. solar thermal program. It summarizes the conclusions of each of the nine technical volumes in the series and offers lessons drawn from the program for future governmental efforts to foster specific technologies.Reading this history, it becomes clear that what was unique about the federal solar program was its attempt to create research guidelines that included commercialization as part of the expected outcome. The three contributors, all active participants in the solar project, are quite candid about what worked and what did not (and why). The result is a tale of bureaucracy and politics worth pondering as we debate the proper relationship between government and science.
Preface and Acknowledgments / Donald A. Beattie and Frederick H. Morse -- Series Acknowledgments / Charles A. Bankston -- 1. About this Volume / Charles A. Bankston and Donald A. Beattie -- 2. About this Series / Charles A. Bankston --
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/23/2015.
Keywords: Solar heating -- History; Solar heating; Solar energy -- History; Solar energy; Electronic books